Oryginalny dokument literacki z życia dawnej Łodzi - cykl Antoniego Sygietyńskiego "Znasz-li ten kraj?" - Janus, Karolina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
At the end of the nineteenth century, the main source of information about the city of Łódź were not local periodicals (as there were no such publications), but correspondence printed in Warsaw papers. Apart from regular reports, m years 1898 and 1899, in one of leading Warsaw daily papers, Kurier Warszawski, there appeared a series of articles under the title “Znasz-li ten kraj?” signed by Antoni Sygietyński. It was the aftermath of the writer’s visit in Łódź (as it was noticed in Goniec Łódzki, Sygietyński arrived in the city on 3rd of December 1889). The reports concerning the life of the textile city appeared in six issues of Kurier Warszawski, dated from 5th, 6th , 15th and 17th of December 1989 and from 6th and 8th of January in the next year.The author of Na skałach Calvados underlined that the title of the series is not unintentional, because Łódź, according to him, was a fully developed city, which had vast contacts with other regions of the world (Russia, Far East, South and North America) rather than with the rest of Polish cities. The writer compares Łódź to a mushroom, which develops rapidly in favourable conditions, whereas in unfavourable circumstances it becomes a latent form of life. Sygietyński underlines also that the city’s growth and organization reminds an American model. The writer attempts to change a stereotypical opinions about the city, mainly concerning its rapid development of industry, huge number of inhabitants or a triplenational character of the textile metropolis. The author aims at acknowledging a true Lodzermensch, he scrutinizes the cultural life of the city.During his visit in Łódź Sygietyński took part in the opening night of Hauptman’s Dwór zatopiony, and in Christmas party in a catholic shelter for children. The meeting with the youngest citizens gave an opportunity for a closer examination of the conditions they lived in as well as of the financial straits their caretaker, Father Szmidel, was facing. The experience triggered an idea of a charity concert, which Sygietyński decided to organize in Łódź The income was donated for modernization of the shelter. The concert was organized on 25th of March 1899 with the participation of the most famous Warsaw artists (Kruszelnik Borcewicz, Michałowski, Wierzbiłowicz, Trenkiel). Such was the social and cultural scale of the event that it was reported in a number of newspapers. Głos underlined Sygietyński’s input into organization by describing him as „a moral impresario of the show” . The author of Wysadzony z siodla while organizing the concert had two main aims: first - to collect money for the shelter, and the second - to arouse a passion for art among the citizens of Łódź.